A Systematic Review of Performance Ultrasound Diagnostic in Acute Cholecystitis - Reynanta; Agustina (The Indonesian Journal of General Medicine, 2024)
Background: One of the most common causes of patients presenting to the emergency department with complaint of abdominal pain is acute cholecystitis. Acute cholecystitis, which is an inflammatory disease of the gallbladder, is mostly due to presence of a stone, ischemia, movement disorders in gallbladder and biliary tracts, and obstruction of the tracts by a tumor. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: Diagnosing cholecystitis and appendicitis with ultrasound is more challenging for internist, surgeons and radiologists. We believe that ultrasound could be used as an adjunct to the clinical examination with the possibility to confirm but not exclude these diagnoses.